2020
DOI: 10.1002/tcr.202000134
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Transformations of Sulfoximines

Abstract: Sulfoximines are widely used as medicines, agricultural chemicals, chiral precursors, and chiral ligands in asymmetric synthesis, as well as pivotal intermediates for the construction of heterocyclic compounds. NH‐sulfoximines may be synthesized from thioethers, sulfoxides, sulfilimines, and sulfinamides. NH‐sulfoximines can undergo various transformations, such as arylations, alkylations, vinylations, and alkynylations. Here, we review the methods that have been applied to the syntheses and transformations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(29 citation statements)
references
References 190 publications
0
29
0
Order By: Relevance
“…In 2018, the chiral Cp/Rh­(III) complex catalyzed desymmetrizing C–H activation of diphenyl sulfoximines was reported by Cramer and Li groups independently (Scheme b). , Very recently, Shi reported a related, elegant Ru-based C–H activation strategy . However, these strategies were limited to cyclic sulfoximines and restricted the further diversification of the product . Hence, the development of new asymmetric catalytic methods for the synthesis of free N–H sulfoximines remains an unrealized target.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2018, the chiral Cp/Rh­(III) complex catalyzed desymmetrizing C–H activation of diphenyl sulfoximines was reported by Cramer and Li groups independently (Scheme b). , Very recently, Shi reported a related, elegant Ru-based C–H activation strategy . However, these strategies were limited to cyclic sulfoximines and restricted the further diversification of the product . Hence, the development of new asymmetric catalytic methods for the synthesis of free N–H sulfoximines remains an unrealized target.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the construction of enantioenriched pyridine derivatives has gained increased attention in the past year. , We recently reported that bis­(pyridine)­s connected to a prochiral carbon center could undergo desymmetrization through selective mono-oxidation using an aspartic acid (Asp)-peptide catalyst with excellent enantiocontrol (up to 99:1 er) . This strategy was also successfully applied to the asymmetric synthesis of helically chiral analogs of loratadine, the active ingredient of Claritin (Scheme c). , Given this result, we were curious about the performance of prochiral bis­(pyridyl)- S -centered substrates with our versatile Asp-peptide catalysts. We decided to explore the catalytic asymmetric synthesis of sulfoximines due to the lack of successful examples in this field. However, the long C–S bond would make it more difficult for the catalyst to differentiate the two pyridine rings, which makes the enantiocontrol a great challenge (C–S length: 1.759 Å vs C–C length: 1.520 Å; see Supporting Information, page 66) . Furthermore, the electron-withdrawing sulfoximine substituent could reduce the nucleophilicity of the pyridine nitrogen, resulting in lower reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most convenient ways to synthesize chiral SOIs involves the formation of a sulfur–nitrogen bond between chiral SOs and nitrenes, either using metal-catalyzed procedures (Fe, Rh, and Ag) or hypervalent iodine or bromine reagents (Figure f). Other approaches involve stereospecific oxidation of enantioenriched sulfinimines (Figure g), desymmetrization of homochiral SOIs , (Figure h), and stereospecific Salkylation of chiral SOIs (Figure i) …”
Section: Introductionmentioning
confidence: 99%
“…Sulfoximines have recently regained popularity as an important functional group in drug discovery and medicinal chemistry (1)(2)(3)(4)(5)(6)(7). The functional group, when added to lead compounds for generating analogues, has shown to increase chemical and metabolic stability and improve solubility (1,2,5).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we have explored the photochemistry of Nphenyl dibenzothiophene sulfoximine [5-(phenylimino)-5H-5k 4 dibenzo[b,d]thiophene S-oxide, 1] (74), which represents a combination of the core structures of dibenzothiophene-S-oxide (DBTO, 2) and N-phenyl iminodibenzothiophene (3) (Scheme 2). This resemblance in the core structure of sulfoximine 1 with compounds 2 and 3 presents the framing of a hypothesis wherein 1 generates the reactive intermediates, nitrene and O( 3 P), upon photoirradiation (Scheme 2, eqs.…”
Section: Introductionmentioning
confidence: 99%